T-cell receptor Vβ skewing frequently occurs in refractory cytopenia of childhood and is associated with an expansion of effector cytotoxic T cells: a prospective study by EWOG-MDS - Aalbers, A M (Nature Publishing Group, 2014)
Immunosuppressive therapy (IST), consisting of antithymocyte globulin and cyclosporine A, is effective in refractory cytopenia of childhood (RCC), suggesting that, similar to low-grade myelodysplastic syndromes in adult patients, T lymphocytes are involved in suppressing hematopoiesis in a subset of RCC patients. However, the potential role of a T-cell-mediated pathophysiology in RCC remains poorly explored. In a cohort of 92 RCC patients, we prospectively assessed the frequency of T-cell receptor (TCR) β-chain variable (Vβ) domain skewing in bone marrow and peripheral blood by heteroduplex PCR, and analyzed T-cell subsets in peripheral blood by flow cytometry. TCRVβ skewing was present in 40% of RCC patients. TCRVβ skewing did not correlate with bone marrow cellularity, karyotype, transfusion history, HLA-DR15 or the presence of a PNH clone. In 28 patients treated with IST, TCRVβ skewing was not clearly related with treatment response. However, TCRVβ skewing did correlate with a disturbed CD4(+)/CD8(+) T-cell ratio, a reduction in naive CD8(+) T cells, an expansion of effector CD8(+) T cells and an increase in activated CD8(+) T cells (defined as HLA-DR(+), CD57(+) or CD56(+)). These data suggest that T lymphocytes contribute to RCC pathogenesis in a proportion of patients, and provide a rationale for treatment with IST in selected patients with RCC.